2000
DOI: 10.1109/76.836282
|View full text |Cite
|
Sign up to set email alerts
|

How to realize a natural image reproduction using stereoscopic displays with motion parallax

Abstract: In order to achieve a realistic image representation with a high degree of telepresence, stereoscopy is known as a very powerful means. Motion parallax is another important visual cue. It contributes to the naturalness of vision and can reduce artifacts of common stereoscopic representation techniques. This paper focuses on the ratio of (real or virtual) camera movement to head movement ("gain of motion parallax") and on the image reproduction conditions that allow perceiving a stable and natural stereoscopic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 10 publications
0
5
1
Order By: Relevance
“…However, the prototype provided motion parallax in the horizontal plane only. Nonetheless, all three dimensions of head movements of the observer are necessary when reproducing motion parallax . In addition, none of the present studies indicated the ratio of the head movement to the laparoscope movement, which is significantly different from a regular stereo vision system.…”
Section: Introductioncontrasting
confidence: 68%
See 3 more Smart Citations
“…However, the prototype provided motion parallax in the horizontal plane only. Nonetheless, all three dimensions of head movements of the observer are necessary when reproducing motion parallax . In addition, none of the present studies indicated the ratio of the head movement to the laparoscope movement, which is significantly different from a regular stereo vision system.…”
Section: Introductioncontrasting
confidence: 68%
“…In the typical stereo vision system, to obtain an undistorted reproduction of motion parallax, the ratio of the camera movement distance k to the head movement distance w is required to be 1:1. Runde proposed the ratio ‘gain of motion parallax’, which should be adjustable by the viewer, and for most observers, the preferred gain was approximately 0.75.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Runde pointed that the number of views per degree of viewing angle should be above 12 [12]. To select the appropriate value of N, here, we take a spatial straight line as an example.…”
Section: Resultsmentioning
confidence: 99%